Updated Common Evaluation Framework For IMF Capacity Development And Guidance Note. (Policy Papers; Policy Paper, 2020)
This document updates the Common Evaluation Framework (CEF) for the Fund's capacity development (CD) activities and provides practical guidance on its implementation. Since its adoption, the Fund has made progress in implementing the CEF. However, areas for improvement remain. The document aims to address these areas, drawing on lessons from experience with evaluations since the CEF's adoption.